2012
DOI: 10.1165/rcmb.2011-0224oc
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endoplasmic Reticulum Stress in Age-Related Susceptibility to Lung Fibrosis

Abstract: The incidence of idiopathic pulmonary fibrosis (IPF) increases with age. The mechanisms that underlie the age-dependent risk for IPF are unknown. Based on studies that suggest an association of IPF and gherpesvirus infection, we infected young (2-3 mo) and old (>18 mo) C57BL/6 mice with the murine gherpesvirus 68. Acute murine gherpesvirus 68 infection in aging mice resulted in severe pneumonitis and fibrosis compared with young animals. Progressive clinical deterioration and lung fibrosis in the late chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
101
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 119 publications
(107 citation statements)
references
References 37 publications
4
101
2
Order By: Relevance
“…We found that chrysotile exposure increased expression of various chaperone genes (endoplasmic-resident protein 72, GRP94, and protein kinase inhibitor 58-kDa) as well as other ER stress markers including ERO1-␣ and CHOP. Prior studies have evaluated the role of ER stress in inducing apoptosis in AEC as a potential mechanism in the pathogenesis of pulmonary fibrosis (8,9,11,12,34). Our findings clearly reveal ER stress in chrysotile-exposed macrophages; however, we found no significant apoptosis in alveolar macrophages from chrysotile-exposed mice.…”
Section: Discussioncontrasting
confidence: 43%
See 3 more Smart Citations
“…We found that chrysotile exposure increased expression of various chaperone genes (endoplasmic-resident protein 72, GRP94, and protein kinase inhibitor 58-kDa) as well as other ER stress markers including ERO1-␣ and CHOP. Prior studies have evaluated the role of ER stress in inducing apoptosis in AEC as a potential mechanism in the pathogenesis of pulmonary fibrosis (8,9,11,12,34). Our findings clearly reveal ER stress in chrysotile-exposed macrophages; however, we found no significant apoptosis in alveolar macrophages from chrysotile-exposed mice.…”
Section: Discussioncontrasting
confidence: 43%
“…6F). Because ER stress has been linked to increased apoptosis in AEC (8,9,11,12) in fibrotic lung, we determined if ER stress was associated with increased apoptosis in mouse BAL cells. There was no difference in apoptosis in alveolar macrophages from chrysotile-or TiO 2 -exposed mice, as measured by caspase-3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Senescence, mitochondrial dysfunction, and insufficient autophagy in the aging lung might have implications in maladaptive responses to stress. For instance, elderly mice are more vulnerable to fibrosis after injury or stress (17,21,22) and have a lower capacity for normal repair after damage (23). In this context, our group has shown that the lung's protective mechanisms against injury, such as mesenchymal stem cell differentiation, are also impaired with age (24).…”
mentioning
confidence: 99%